Thermal degradation behavior of pectin in citrus wastes with density functional theory study. (15th April 2019) - Wu, Jie; Liu, Chao; Xu, Xiaoxiao; Li, Qinbin; Li, Xiaoxiao
Highlights: Detailed decomposition pathways of pectin are proposed. Rate controlling steps of major products are clarified through kinetic analysis. Relatively optimal pathways of the formation of major products were proposed. Formation condition of methane and methanol is verified. Abstract: Citrus wastes contain large amounts of pectin as the main constituent in addition to cellulose, lignin and hemicellulose. The thermal degradation behaviors and products distribution from the fast pyrolysis of citrus wastes are different from lignocellulosic biomass due to the high content of pectin. In view of this, the detailed decomposition behaviors of pectin are investigated by using density functional theory (DFT). The calculation results indicate that the most energetically favored initial reaction of pectin is the cleavage of α-1, 4-glycoside bond (C1 O bond) with an energy barrier of 126.4 kJ/mol. In addition, compared with the reaction energy barriers, it can be seen that the formation of CO, CH4 and furan are more difficult than that of CO2, methanol and furfural, respectively. The comprehensive kinetic analysis indicates that Path-A2 -2 should be the most favorable pathway for the formation of acetaldehyde. The rate-determining steps of the formation of furan and furfural are dehydration reactions while decarbonylation reaction is the result of the rate-determining step of the formation of methyl 2-furoate and propanone.